Small and medium multifamily housing: affordability and availability. Issue 7 (9th August 2022) - An, Brian Y.; Bostic, Raphael W.; Jakabovics, Andrew; Orlando, Anthony W.; Rodnyansky, Seva
Abstract: Housing units in small and medium multifamily (SMMF) properties, defined as buildings with 2 to 49 units, comprise over 20% of the U.S. housing stock. Using the American Community Survey and American Housing Survey, this study fills an important gap in the literature by examining the affordability and availability of these housing units. This analysis reveals that SMMF units contain the largest percentage of the lowest-income households and the majority of rental units across the country. It employs models of filtering and quality-adjusted rents to decompose the factors that make these units accessible to such households. Even after controlling for these factors, their affordability persists, and their market share is declining. These findings raise concerns about the future availability of these affordable units. Policy-relevant conclusions are drawn about their role in the future of local, regional, and national economies.